The application of caveat emptor and caveat venditor doctrines from civil and Islamic perspectives - Muhammad Hafiz Mohd. Shukri,; Rahmah Ismail,; Ruzian Markom, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Since a long time ago, consumers have never been completely safe from exposure to the risk of purchasing defective products, which may cause an adverse effect on them. The introduction of the doctrines of caveat emptor and caveat venditor became a part of the common law to resolve disputes between manufacturers, sellers, and consumers. This study therefore aims to analyze the application of the caveat emptor and caveat venditor doctrines according to civil and Islamic perspectives to see how far the application of both doctrines can provide justice to consumers. Utilizing doctrinal approach based on the methodology of qualitative legal research, this study involves in-depth analysis of statutory provisions, court cases, Quranic texts, hadiths, and the opinions of Muslim scholars. The research findings were analyzed through content analysis and critical analysis methods. This study has proven that there are legal problems with regards to the application of the caveat emptor doctrine and its resulting negative impact on consumers, thus leading to the formation of the caveat venditor doctrine. Although the term “caveat venditor” and its definition are not expressly mentioned in the Qur’an and the hadiths, the application of the doctrine is seen to have a strong foundation in Islam. The results of this study are expected to contribute significant new knowledge in the field of consumer law since a comparative analysis of the application of both doctrines according to civil and Islamic perspectives is still lacking, especially in cases involving the selling of defective products.